Sentence-level consistency of conformer based pre-training distillation for Chinese speech recognition - Li, Haifang; Tang, Chao; Yue, Xin; Li, Xu (Frontiers in Communications and Networks, 2025)
IntroductionWe address robustness and efficiency in Chinese automatic speech recognition (ASR), focusing on long-form broadcast speech where sentence-level semantic consistency is often lost.MethodsWe propose a Conformer-based framework that integrates sentence-level consistency with pre-training knowledge distillation. We also construct CH Broadcast ASR, a domain-specific Chinese corpus for the broadcast and television domain, and evaluate on AISHELL-1, AISHELL-3, and CH Broadcast ASR.ResultsThe proposed model consistently outperforms strong baselines (TDNN, DFSMN-T, TCN-Transformer), achieving CER = 3.3% on AISHELL-1, 3.7% on AISHELL-3, and 3.9% on CH Broadcast ASR, while reducing model size by >10%.DiscussionEnforcing sentence-level semantic alignment together with distillation improves robustness for long-form broadcast speech and enhances efficiency for real-time deployment.